Yin-Yang concept of healing in Tan Twan Eng‟s trauma fictions - Hou, Xia; Omar, Noritah; Kaur, Hardev; Bahar, Ida Baizura (Sciedu Press, 2023)
Contemporary Malaysian literature not only provides a platform of lives, but also functions as an avenue for trauma expressions where writers utilize different narrative strategies to create characters with multiple identities. One of the prominent Chinese-Malaysian contemporary writers Tan Twan Eng deals with the traumatic impact brought by Japanese oppression to Malaya during the 1940s and he offers a traditional Chinese vision of understanding on healing of trauma. His writing offers a unique and compelling perspective on the complexities of identity, memory, and trauma, and has earned him a place as one of the most important contemporary writers from Malaysia. In his works, the Yin-Yang concept can also be applied to the healing of trauma, as it emphasizes the importance of finding balance and harmony between opposing forces in order to achieve wholeness and well-being. Deploying the Yin-Yang concept, he examines how the protagonists in The Gift of Rain (2007) and The Garden of Evening Mists (2012) deal with traumas of war and violence. This paper utilizes Lacapra‟s “work through”, instead of merely attempting to ignore or repress the painful events, confronting them in a way that enables people to process and integrate them, Cathy Caruth‟s trauma theory about timelessness, relatedness, repetition and intrusiveness and Chinese traditional concept of Yin-Yang to analyze the ways of healing traumas. The transition from traumatic memory to narrative memory, in fact is the balance of forgetfulness and remembrance, and balance of mental pain and peace. His application of the Yin-Yang principles provides a potent metaphor for the process of achieving harmony and balance in the face of traumas. His Yin-Yang concept of trauma healing places a strong emphasis on the significance of confronting the past in a way that allows for the integration and transformation of traumatic events while also acknowledging the wider social and cultural settings of trauma. The research may provide a new and harmonious perception to understand traumas.